Pharmacological targeting of bone marrow mesenchymal stromal/stem cells for the treatment of hematological disorders - Noriko Sugino; Tatsuo Ichinohe; Akifumi Takaori-Kondo; Taira Maekawa; Yasuo Miura (BMC, 2017)
Abstract The therapeutic effects of mesenchymal stromal/stem cells (MSCs) are mainly based on three characteristics: immunomodulation, tissue regeneration, and hematopoietic support. Cell therapy using culture-expanded MSCs is effective in some intractable bone and hemato-immune disorders; however, its efficacy is limited. In this article, we review the previous efforts to improve the clinical outcomes of cell therapy using MSCs for such disorders. We describe pharmacological targeting of endogenous bone marrow-derived MSCs as a crucial quality-based intervention to establish more effective MSC-based therapies.